BOARD STRUCTURE AND ISLAMIC BANK STABILITY: A STANDALONE RISK COMMITTEE MODERATING EFFECT - Umar, Umar Habibu; Abduh, Muhamad; Besar, Mohd Hairul Azrin; Kurawa, Junaidu Muhammad (Journal of Islamic Monetary Economics and Finance, 2024)
This study investigates the impact of board attributes on the stability of Islamic banks and whether the presence a standalone risk management committee (SARC) moderates their relation. Applying the feasible generalized least squares (FGLS) regression as well as the two-step system generalized method of moments (GMM) estimator for robustness to a panel sample of 43 Islamic banks across 15 countries over eleven years from 2010 to 2020, we document evidence suggesting that board meetings, board gender diversity and foreign directors do not influence the stability of Islamic banks. Conversely, board members holding doctorate degrees (PhDs) significantly and negatively affect the stability of Islamic banks. In addition, the presence of SARC significantly improves the stability of Islamic banks. The study further finds that SARC partially and positively moderates the effects of board members with PhDs and foreign directors on the stability of Islamic banks.